French scholars’ contributions to the study of the Swahili language : the case of Charles Sacleux (1856-1943) - (:unkn) unknown (My University, 2013)
Following a research undertaken in archives, libraries as well as through interviews, the author describes the Swahili coast and the contact between Swahili and Europeans. While analyzing available early documents published by French researchers, he chronologically depicts endeavour and challenges of studying African languages during that era. Among them, Charles SACLEUX, a Spiritan priest performed an outstanding work especially in etymology, dialectology, lexicography and in ethno-linguistics. The study presents his biography together with his philosophical and methodological approaches. The findings show that in comparison with other researchers who, for the sake of standardizing the language, used a prescriptive approach, he opted for a descriptive. His publications present the language in its natural state. Together with Sacleux’ work, to complete the account, the thesis reserves one chapter for the current progress in teaching/learning as well as publishing on Swahili in France. The insights from the study suggest that it is important that some contents from Sacleux’ publications be revised and incorporated in contemporary Swahili literature.
Keywords: African Research